Teaching engineers to be persuasive - Griffith-Bourn, Mary Margaret (My University, 2022)
This study highlights an innovative educational project entitled ‘Dynamic Teaching through Communication Skills’ as well as forming part of joint initiative for Erasmus + Communities and Students Together (CaST) 2019-1-UK01-KA203-061463. The case study shows that there are many ways to approach teaching through a second language within the framework of subjects not usually taught through a second language. The proposal includes discussions on the practical methodology of integrated content and language in higher education (ICLHE). While bringing real world problem solving into the Health Engineering degree, the presentation underscores aspects of persuasion and pitch development in within the paradigm of English as a Lingua Franca. The goal is to incorporate communication strategies into an engaged learning initiative so as to better prepare students for the work place as they search for answers to real-world problems. This highly interdisciplinary project focused on students from the Health Engineering Degree and more specifically those from outside language areas because we feel they are blatantly missing in many of the discussions about the practical bilingual implementation at the university (ICLHE). Students were asked to create a data management project as related to healthcare and present it using a pitch. Several support workshops were offered to aid them in their pitch development. Research has shown, the entrepreneurial pitch has well-marked structural features, specific themes and figures of speech, and it is manifestly persuasive in intention . The focus of this case study is how we incorporated a pitch into a project based learning initiative.
Keywords: Persuasión (Retórica); Persuasive discourse; Engaged learning; Health engineering; Upskilling; Communication strategies